GEOCHRONOLOGY: LINKING THE ISOTOPIC RECORD WITH PETROLOGY AND TEXTURES - AN INTRODUCTION - Vance D.; Müller W.; Villa I.M. (My University, 2003)
One of the key aims of geochronology, and the subject of the papers in this Special Publication, is the linkage of isotopic ages to petrological and textural information. A close link between the two types of information greatly improves the constraints available from geochronologgy on the nature and rates of lithospheric processes such as metamorphism and deformation. There have been several key advances in this area over the past 10-20 years, relating to increased precision and accuracy of isotopic ages but also, and crucially, to the spatial resolution available to geochronologists. This resolution now approaches that on which petrological, chemical and textural information is obtained. We also, in this introduction, identify the barriers that have impeded further progress, which relate both to technical issues as well as to problems of understanding. Finally we set the papers in this volume in the context of the preceding discussion and outline the key ways in which these papers point towards further progress in the future.